2012
DOI: 10.3758/s13423-012-0293-z
|View full text |Cite
|
Sign up to set email alerts
|

Do not cross the line: Heuristic spatial updating in dynamic scenes

Abstract: In two experiments, we examined the spatial integration of two viewpoints onto dynamic scenes. We tested the spatial-alignment hypothesis (which predicts integration by alignment along the shortest path) against the spatialheuristic hypothesis (which predicts integration by observation of the left-right orientation on the screen). The stimuli consisted of film clips comprising two shots, each showing a car driving by. In Experiment 1, the dynamic scenes were ambiguous with regard to their interpretation: The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
4
15
0
Order By: Relevance
“…As a result, both the number of nodes and the number of possible cardinal directions are kept at a minimum in SARF CD . Given SARF CD 's success in accounting for human spatial reasoning behavior, our work supports and complements existing findings on the economic nature of human spatial information processing (Huff & Schwan, ).…”
Section: Conclusion and Contributionssupporting
confidence: 82%
“…As a result, both the number of nodes and the number of possible cardinal directions are kept at a minimum in SARF CD . Given SARF CD 's success in accounting for human spatial reasoning behavior, our work supports and complements existing findings on the economic nature of human spatial information processing (Huff & Schwan, ).…”
Section: Conclusion and Contributionssupporting
confidence: 82%
“…As a result, greater updating occurs with greater discontinuity of the incoming information given the preceding context (Huff, Meitz, & Papenmeier, ; Magliano & Zacks, ). For example, updating of situational changes may occur across dimensions of characters, spatial locations, or event information, as posited by theories of visual and verbal narrative (Bateman & Wildfeuer, ; Hoeks & Brouwer, ; Huff & Schwan, ; Magliano, Miller, & Zwaan, ; Saraceni, ; Stainbrook, ; Zwaan & Radvansky, ). Because a situation model is always being built in reference to a progressing (visual) discourse, such updating processes occur iteratively at each unit of a (visual) discourse, not just to incongruities.…”
Section: Semantic Processingmentioning
confidence: 99%
“…If, however, event segmentation is a general perceptual and cognitive process that is independent of the stimulus' modality, we expect event segmentation to be comparable between experimental conditions. Bordwell, 2002) and mean length of event segments (between 5 and 60 seconds, depending on the nature of the stimulus material; e.g., Huff & Schwan, 2012;Zacks, Speer, & Reynolds, 2009) were used to estimate the appropriate duration of the stimulus material to get a sufficient number of event boundaries. This resulted in a duration of the clips between 5 and 6 minutes.…”
Section: Experiments 1: Segmentationmentioning
confidence: 99%
“…The impression of the chase is distorted. For visual dynamic scenes, it was shown that the mere spatial positioning of cameras influences the perception of continuity (Huff & Schwan, 2012). Baker and Levin (2015) have shown that observers' ability to detect changes across filmic cuts depended on the cameras' positions.…”
Section: Theoretical Implicationsmentioning
confidence: 99%